Retention of basic life support in medical students of Airlangga University - Inna Maya Sufiyah; Bambang Pujo Semedi; Sundari Indah Wiyasihati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Cardiac arrest is one of the leading cause of death in the world with steadily increasing number over the years. Basic life support has been proven to lower the risks of tissue damage and further complication. Several study shows that BLS skill are lacking in some doctors and nurses.Objective: Therefore, the purpose of this study is knowing the retention of basic life support in medical student of Airlangga University.Methods: This descriptive study used cross sectional design. Subjects were students at faculty of medicine in Airlangga University who trained one year ago and completed their study of Basic Life Support. Fifty two subject were asked to practice their BLS techniques then scored based on modified American Hearth Assosiation (AHA)’s Basic life support skill checklist.Results: Based on the data, the percentage of students who did the retest correctly: response checked by shouting 92.31% students, response checked by tapping 69.23% students, call for help 44.23% students, airway checked 48.08% students, breathing checked 46.15% students, correct hand placement 100% students, compression rate 78.85% students, compression ratio 75% students, position 94.23% students, and compression depth 78.85% students. Conclusion: One year post training and test, 14 from 52 students could complete all the steps in basic life support skill. Less than a half of the students successfully done 3 out of 10 points that were being tested. Meanwhile, many aspects in circulation point show higher results all above 75%.